IMPLEMENTASI KEBIJAKAN TENTANG UPAYA PEMBERANTASAN PENYAKIT DEMAM BERDARAH DENGUE DI KOTA PEKANBARU - Novriadi "; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Dengue Haemorrhagic Fever (DHF) is a dangerous fever disease that influenced by dengue virus, that went into human blood circulation through the bite of mosquito from Denus Aedes, such as Aedes Aegypti or Aedes Alpopictus. The Government of Pekanbaru City, through Health Department of Pekanbaru City still trying to Eradicate Dengue Haemorrhagic Fever. That efforts included in the Judgement of Health Ministry of Republic Indonesia Number 581/Menkes/SK/VII/1992 about Eradicate Dengue Haemorrhagic Fever. The objective of this research is to determine how implementation and factors that influence the Implementation of Attempts to Eradicate Dengue Haemorrhagic Fever Policy at Pekanbaru City.Theoretical concept used is theory of implementation based from George C. Edward III. The implementation approach includes communication, resources, disposition, and bureaucracy structure factors. This research used qualitative method with descriptive data assessment. In collecting data, researcher use methods of interview, observation, and documentation with snowball sampling method as the source of information and data analyzing with descriptive qualitative method.The result of this research showed that Implementation of Attempts to Eradicate Dengue Haemorrhagic Fever Policy was not effective yet because the Health Department of Pekanbaru City was not optimum enough in did their program, this matter because the information was not clear enough for the society, and available estimate, and there is still no of Standard Operational Prosedure (SOP).Keyword: Implementation, Eradicate, Dengue Haemorrhagic Fever